Compliance Audit of Safety, Health, Environment and Services at Selected Ecotourism Sites in Malaysia - Oyop, Siti Mastura (2006)
The purpose of this research is to evaluate the compliances on Safety, Health, Environmental and Services (SHE) parameters in ecotourism sites. A number of ecotourism sites in Peninsular Malaysia were chosen randomly for analysis. The success indicators were identified for each parameter and data of evaluation activities were gathered by using a checklist to quantify the performances of the 17 selected ecotourism sites. The evaluation focuses on the relevant practices and consistency of the environmental management system towards sustainable ecotourism that was applied on-site.